Optimalisasi Pemanfaatan Lahan Pekarangan Untuk Menumbuhkan Ketahanan Pangan Rumah Tangga Dimasa Pandemi Covid-19 - Maulidiyah, Rafiqah; Iqbal (Abdi Techno, 2021)
Covid-19 is a disease caused by the acute respiratory syndrome corona virus 2 (SARS-CoV-2) and can be transmitted from one human to another through coughing / sneezing (droplets), not through the air. As a result of the Covid-19 pandemic, various policies were implemented to break the chain of the spread of the Covid-19 virus in Indonesia, one of which was the implementation of physical distancing. This has an impact on one of the sectors in Indonesia, namely the agricultural sector in terms of fulfilling community food. Efforts to foster household food security can be made by optimizing the use of yard land as a source of food. This community service activity aims to invite the people of Banyorang Village to optimize the use of their yards as a source of food. This activity was carried out by using the method of making a demonstration plot for farm yards and recording a video of the activity which was then published on YouTube so that it could be watched by the community, especially the people of Banyorang Village. The result of this activity is to raise public awareness in utilizing yard land and obtaining food from the yard. This activity is carried out from home so that in addition to meeting food needs, it can also minimize the spread of covid-19.